PERAN PUSAKA SAKINAH DALAM UPAYA PENURUNAN ANGKA PERCERAIAN DI KUA BESUK KABUPATEN PROBOLINGGO - Wafa, Muhammad Ali; Quthny, Abu Yazid Adnan; Syafi’i, Imam (LPPM STAI Muhammadiyah Probolinggo, 2023)
The Ministry of Religion, in response to the high divorce rate, has undertaken various initiatives aimed at sustaining family resilience. One such initiative is the Sakinah Family Service Center Program (Pusaka Sakinah), which seeks to enhance the role of the KUA in safeguarding Indonesian families from divorce. This article emphasizes the need to assess the implementation of the Pusaka Sakinah program by the KUA, including the strategies for advancement and the execution of counseling programs. Employing qualitative methods, this research conducted case studies focused on KUA Besuk. The study revealed several key findings: firstly, while enhancing the KUA's role in fostering sakinah families is achievable through the Pusaka Sakinah program, ensuring the sustainability of the program is challenging due to the KUA's heavy reliance on external funding. Secondly, there are limited initiatives and innovations because the concept of the Pusaka Sakinah program is not fully comprehended and has been misinterpreted during the restructuring of KUA, resulting in confusion, reduction, and even rejection of programs perceived as burdensome by KUA. Thirdly, there is still inadequate synergy in the implementation of the program with similar initiatives undertaken by other ministries and local governments. Keywords: Pusaka Sakinah; Wedding; Divorce.